Are the alarm calls of North American red squirrels (Tamiasciurus hudsonicus) functionally referential? - Digweed, Shannon; Rendall, Drew (My University, 2009)
North American red squirrels are a small-bodied and solitary-living species that faces a diversity of predators and produces two different variants of alarm calls in response to them. Recent studies have yielded conflicting interpretations of the predator-specific and functionally referential nature of these alarm call variants. We undertook a systematic set of playback experiments to quantify the responses of red squirrels to alarm calls produced by other squirrels during encounters with different predators. The experiment was designed to test a core requirement of functionally referential alarm calls, namely that different alarm call types induce distinct and functionally appropriate escape responses in listeners. Results indicated that squirrels registered and responded to alarm calls produced by others; however, their responses were not differentiated according to the type of alarm call they heard and thus did not provide evidence that the different alarm call variants hold any predator-specific, referential value. These outcomes are discussed in light of complementary work on alarm call production in red squirrels and broader aspects of this species’ life history in an effort to better understand the necessary and sufficient pressures promoting the evolution of referential call systems in animals.
Keywords: alarm calls; communication; red squirrels; functional reference